Measuring changes in face-to-face interaction between teachers and students using a sociometric sensor device after teacher training - Nakao, Tomoko; Fujino, Haruo; Yamamoto, Tomoka; Ishii, Atsuko; Taniike, Masako; Okuno, Hiroko (Frontiers in Education, 2025)
IntroductionTeacher training (TT) was developed to improve teachers’ skills in interacting with students with neurodevelopmental disorders. Teachers can also apply these skills to students without neurodevelopmental disorders in their classrooms. Therefore the interaction between teachers and students would change before and after the TT. However, prior studies have not utilized objective tools to assess the changes in interactions caused by TT interventions. In this study, a wearable sociometric sensor device was used to assess the changes in face-to-face interactions during a group classroom activity to provide objective measures of interactions.MethodsWe evaluated face-to-face interactions using sociometric devices in six classes, a total of six teachers and 158 elementary school students, during a group activity task. An evaluation of teacher-student interactions by video recording was also used to examine the directions of changes in interaction time between the sociometric device and video recording.ResultsThe changes in face-to-face interaction time between teachers and students were in the same direction in five of six teachers. The TT intervention did not significantly affect the interaction time in the current study.DiscussionBased on the results, a wearable sociometric sensor device can serve as an objective measure for detecting changes in classroom interactions.